Geo-didattiche per il futuro. La geografia alla prova delle competenze - Zanolin, Giacomo (Tratti geografici. Materiali di ricerca e risorse educative, 2017)
This volume comes from the 4th National Workshop of the Italian Association of Geography Teachers (Milan, 26-27 August 2015) and proposes a reflection shared by scholars and teachers on the potentials and criticalities of teaching geography, facing the present and the future of education.